(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассматриваются вопросы современного развития социально-экономической географии с учетом сложившихся традиций и поиска новых направлений функционирования. Дается оценка советского и постсоветского географического наследия, выявляются тенденции и новации, нацеленные в будущее. Раскрываются теоретико-методологические основы перспективного развития общественной географии, активизации фундаментальных и прикладных исследований. SOCIAL AND ECONOMICAL GEOGRAPHY: TRADITIONS AND MODERN DEVELOPMENT TENDENCIES The problems of social and economical geography’s modern development on the basis of existing traditions and research of new directions of functioning are considered. It is given the estimation of soviet and postsoviet geographical heritage. The article describes theoretical and methodological bases of perspective development of human geography, activation of fundamental and applied researches.